Chikungunya virus outbreak in Sint Maarten, 2013–2014 - Maria Henry; Lorraine Francis; Virginia Asin; Karen Polson-Edwards; Babatunde Olowokure (Pan American Health Organization, 2017)
ABSTRACT This report describes the outbreak of chikungunya virus (CHIKV) in Sint Maarten, a constituent country of Kingdom of the Netherlands comprising the southern part of the Caribbean island of Saint Martin, from 22 December 2013 (first reported case) through 5 December 2014. The outbreak was first reported by the French overseas collectivity of Saint-Martin in the northern part of the island—the first site in the Americas to report autochthonous transmission of CHIKV. By 5 December 2014, Sint Maarten had reported a total of 658 cases—an overall attack rate of 1.76%. Actual prevalence may have been higher, as some cases may have been misdiagnosed as dengue. Fever and arthralgia affected 71% and 69% of reported cases respectively. Of the 390 laboratory-confirmed cases, 61% were female and the majority were 20–59 years old (mean: 42; range: 4–92). The spread of CHIKV to Sint Maarten was inevitable given the ease of movement of people, and the vector, island-wide. Continuing their history of collaboration, the French and Dutch parts of the island coordinated efforts for prevention and control of the disease. These included a formal agreement to exchange epidemiological information on a regular basis and provide alerts in a timely manner; collaboration among personnel through joint island-wide planning of mosquito control activities, especially along borders; notification of all island visitors, upon their arrival at airports and seaports, of preventative measures to avoid being bitten by mosquitoes; dissemination of educational materials to the public; and island-wide public awareness campaigns, particularly in densely populated areas, for both residents and visitors. The information provided in this report could help increase understanding of the epidemiological characteristics of CHIKV and guide other countries dealing with vector-borne epidemics.